Budaya Pecinta Kopi dan Gaya Hidup Urban Kedai Kopi di Surabaya: Analisis Visual Semiotika Spasial - Abduh Rafif Taufani (Jurnal Media dan Komunikasi, 2020)
This research are focused on cultural identity and urban lifestyle that being representated throu symbols on coffeeshops in Surabaya. The research are conducted using vernacular semiotics or better called as spatial semiotic analysis. The researcher are interested due to current trends of third-wave coffeshops and how they identify themselves as a coffee lovers, also how third-wave customers put meaning in urban lifestyle in general throu themselves, visual gimmick, and interior design of the coffeeshops. Vernacular Semiotic are chosen as an analytic instruments because the visual elements surrounding the coffeshops and their customers are treated as visual text. The meaning behind coffee-drinkin activity are actively produced by the urban dwellers that habitate the spatial space of the coffeeshops. This research conclude that urban dwellers/customers are more drawn into the meaning throu visual elements to go to coffeeshops rather than the actual beverages. Therefore urban dwellers are also consuming the meaning behind every activity they are doing. The consumed meaning is either produced by the urban dwellers or the coffeshop itself.